2015
DOI: 10.1016/j.prosdent.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parafunctional loading and prosthetic connection on stress distribution: A 3D finite element analysis

Abstract: Internal connection implants presented the most favorable biomechanical situation, whereas the least favorable situation was the biomechanical behavior of external connection implants. Parafunctional loading increased the magnitude of stress by 3 to 4 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
(39 reference statements)
6
22
0
2
Order By: Relevance
“…The third null hypothesis (that the Morse taper implants would show the same biomechanical efficiency as the external hexagonal implants) was rejected because the Morse taper implants showed better stress distribution in the cortical bone. These results are consistent with recently published studies, which have indicated the best biomechanical profile for this type of connection [4,16,34]. However, unlike previous studies that evaluated only bone tissue [16], this study indicated a significant increase in stresses among the abutments of the Morse taper implants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The third null hypothesis (that the Morse taper implants would show the same biomechanical efficiency as the external hexagonal implants) was rejected because the Morse taper implants showed better stress distribution in the cortical bone. These results are consistent with recently published studies, which have indicated the best biomechanical profile for this type of connection [4,16,34]. However, unlike previous studies that evaluated only bone tissue [16], this study indicated a significant increase in stresses among the abutments of the Morse taper implants.…”
Section: Discussionsupporting
confidence: 92%
“…However, unlike previous studies that evaluated only bone tissue [16], this study indicated a significant increase in stresses among the abutments of the Morse taper implants. These results can be justified by the geometry of the Morse taper implants (an internal connection), which leads to the centralization of stresses along the axis of the implant itself and adequate stability [4,34,35]. Therefore, it causes an increase in stresses in the abutment-implant interface and a reduction of the magnitude of tensions in the cortical bone, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations